TECHNIQUES AND FACTORS CONTRIBUTING TO DEVELOPING CRITICAL THINKING SKILLS - Irina Vladimirovna Glukhova (Образование и наука)
The paper deals with the issue of working out and introduction in educational process of higher educational institutions of the innovative technology for developing skills of critical thinking skills of the future specialists. Research is aimed at revealing of the factors promoting formation of students’ critical thinking in high schools; the search of strategy and the receptions actualizing creative abilities of students and helping to formation of an active, independent person. The author gives the reasoned proving that it’s necessary to set up the creative educational environment and adjustment of positive dialogue between the teacher and the trainee for education of such person, development of abilities of an objective reflection, interpretation of the phenomena, formulations of adequate conclusions, well-founded evaluating. Methods. The methods involve the analysis of the philosophical, psychology-pedagogical, methodical literature and the scientific periodical publications; generalisation of the Russian and foreign background, classification and arrangement of the considered issues, supervision. Results. Current approaches to the rendering of critical thinking and a problem of its formation in the scientific literature are considered; the concept «the creative educational environment» is specified; the ways of increasing the educational process efficiency are shown. Scientific novelty. The complex of procedures and the conditions promoting effective development of critical thinking skills is theoretically proved on the basis of the analysis of various information sources. Practical significance. The research outcomes and the recommended methods of critical thinking skills formation can be useful for the professors and lecturers of higher education institutions to optimize subject matter selection, techniques and methods of education under the conditions of dynamically updated educational process.